THE PROBLEM OF DIPLEXITY / SINGLE-COMPLEXITY OF SENTENCES WITH PREDICTIONS ON –NO, AND -TO IN UKRAINIAN AND POLISH LANGUAGES - Korpalo, Oksana (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2025)
The article deals with the predicative forms with -no, -to endings, which have been vigorously discussed in the history of the Slavic linguistics. Particularly, in the Ukrainian linguistics the contradictory are the questions the necessity or nonnecessity to use sentences with verb forms ending in -no, -to, the questions of their passivity, structure, and synonyms with other syntactical constructions. Instead, in the Polish linguistics most controversial is the question of their subjectivity or non- subjectivity. The aim of this study find out the specifics of semantic subject in sentences with the predicative forms with -no, -to endings in the Polish language, identify the Кlinguistic means by which achieved the expected communicative stylistic effect. The main idea of the article is identify the characteristics of the subject which is characterized by possesses a compulsory belonging to the category of person as well as indefiniteness which is caused by direct or indirect action relations to the personal subject set. It was set up that subject indefiniteness is shown up differently due to the character of the noted actions and speaker’s communicative tasks. Sentences with predicative forms with -no, -to endings , where the subject does not explicate with separate lexeme contains a reference to performers action thanks to the context.